POLA PEMBINAAN NARAPIDANA DI LAPAS KELAS II/B MUARA BUNGO BERDASARKAN UNDANG-UNDANG NOMOR 12 TAHUN 1995 - Siti Maryam; Iskandar AR (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2021)
Correctional institutions are organizations that have the same important duties and functions as other institutions in the Criminal Justice System, such as the Police, Prosecutors and Courts. The duties and functions of the Correctional Institution are to carry out guidance for prisoners and correctional students. The formulation of the problem in this research is what are the patterns, what are the obstacles and what are the efforts of the Class II/B Muara Bungo prison in conducting prisoner development based on Law Number 12 of 1995. The method used is descriptive qualitative. Informants in this study were all Penitentiary Class II/B Muara Bungo and all convicts and ex-convicts. With the number of informants as many as 12 people. The results of the study show that the pattern of fostering prisoners at the Class II/B Muara Bungo prison based on Law Number 12 of 1995 has been implemented well through spiritual development and independence. With the aim of building mental and spiritual as well as developing the potential, talents and interests of prisoners. The results of inmates coaching by the Class II/B Muara Bungo prison can also be said to be quite good because it has been able to improve the abilities and skills of prisoners in various fields of business and has been able to increase the obedience of the prisoners. However, the implementation has not been optimal due to limited facilities and infrastructure, human resources, and low awareness of prisoners to be able to do coaching. Efforts are being made to increase human resources, improve facilities and infrastructure and collaborate with the Bungo Regency Job Training Center, and provide motivation and understanding to prisoners about the importance of coaching programs.